"Thousands of our men are getting practically nothing at all to do": Public Works Relief Programs in Regina and Saskatoon, 1929-1940 - Brennan, Patrick (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1992)
Unemployment relief work programs undertaken in Saskatchewan cities during 1929-32 and 1938-40 were not a failure. Carried out with an unavoidable minimum of "mismanagement" and "waste," they produced useful assets and badly needed employment, and not surprisingly were strongly supported by local taxpayers and the able-bodied unemployed alike. This record and the determined if too often unsuccessful efforts by the administrations and unemployed in Regina and Saskatoon to have even more relief money channelled into such "work and wages schemes" are an indictment of the federal response to the unemployment crisis and the impossible situation in which the flawed doctrine of "local responsibility" placed local governments. As such, the history of these programs serves as a useful corrective to the widespread impression that Prairie cities failed to show sufficient leadership or initiative in dealing with the unemployment crisis during the 1930s.